2005
DOI: 10.1007/s00284-005-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Identification of cry1I Genes in Bacillus thuringiensis Using Polymerase Chain Reaction and Restriction Fragment Length Polymorphism Analysis

Abstract: A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method for detection and identification of cry1I genes from Bacillus thuringiensis (Bt) was established. Based on the analysis of conserved regions of the cry1I genes, 2 oligonucleotide primers were designed to amplify a 665-bp fragment of the genes. The amplification products were digested with restriction endonuclease HinfI or with RsaI in addition for specific detection of different variants from the known subclasses of cry1I ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
1
10
0
5
Order By: Relevance
“…There were no products identified using primer set two or three. Thus, the HD1 strain was determined to contain four cry1-type genes, cry1Aa, cry1Ab, cry1Ac, and cry1Ia, which corresponded with known results (10,20). Strain HD29 produced a cry1Ab gene RFLP pattern (Fig.…”
Section: Resultssupporting
confidence: 71%
“…There were no products identified using primer set two or three. Thus, the HD1 strain was determined to contain four cry1-type genes, cry1Aa, cry1Ab, cry1Ac, and cry1Ia, which corresponded with known results (10,20). Strain HD29 produced a cry1Ab gene RFLP pattern (Fig.…”
Section: Resultssupporting
confidence: 71%
“…Novel primers for the specific detection of vip3A genes were designed following a previously described methodology [Sauka et al, 2006[Sauka et al, , 2007. Primers used for amplification of a vip3Ab,vip3Ad,vip3Ae,vip3Af,vip1Ag and vip1Ah genes were as follows: DS3AF (forward; 5 -GTG AAA ACA AGT GGC AGT G-3 ) and DS3AR (reverse; 5 -TCC GCT TCA CTT GAT TCT ACT-3 ).…”
Section: Detection Of Vip3a Genesmentioning
confidence: 99%
“…The DNA templates for PCR were obtained as previously described [Sauka et al, 2006]. Five microliters of supernatant was used in each reaction.…”
Section: Detection Of Vip3a Genesmentioning
confidence: 99%
“…Twin strains were previously discarded to avoid overestimated distribution of frequencies, using sodium dodecyl sulphate-polyacrylamide gels and PCR (Sauka et al, 2006 (Benintende & Cozzi, 1996), until complete autolysis was observed at 340 rpm and 30°C. Spore-crystal complexes were obtained by centrifugation for 15 min at 12,000 g and 4°C, and pellets were freeze-dried.…”
Section: Bioensaios De Alimentação Induzida Para Determinar a Atividamentioning
confidence: 99%